Aldara®‐induced skin inflammation: studies of patients with psoriasis. (1st February 2015) - Vinter, H.; Iversen, L.; Steiniche, T.; Kragballe, K.; Johansen, C.
Summary: Background: The application of Aldara ® cream containing 5% imiquimod stimulates Toll‐like receptor 7/8 on plasmacytoid dendritic cells, thereby producing a potent immunomodulatory effect. This has been reported to trigger psoriasis. Objectives: To establish a human model of Aldara‐induced psoriasis‐like skin inflammation in patients with psoriasis. Methods: Nonlesional psoriatic skin of 13 patients was treated with Aldara for 2 or 7 days. The skin was evaluated clinically and histologically on days 2, 4 and 7. Cytokine expression in Aldara‐treated, lesional and nonlesional psoriatic skin was compared using reverse‐transcription quantitative polymerase chain reaction. Results: Nine of the 10 patients receiving application of Aldara under occlusion for 2 days developed redness, induration and scaling. Histological analysis revealed focal parakeratosis, acanthosis and perivascular mononuclear infiltration. On days 4 and 7 both clinical and histological signs of inflammation subsided. Two of the three patients treated with Aldara for 7 days developed erosions leading to psoriasis on day 21. Cytokine markers of activation of the innate immune system [interferon‐α, interferon regulatory factor‐7 and interleukin (IL)‐1β] were equally expressed in lesional and Aldara‐treated skin ( n = 6). IL‐6 and tumour necrosis factor‐α were preferentially expressed in Aldara‐treated skin. Adaptive immune system activation occurred only partially: IL‐23p19 and IL‐22 were similarly overexpressed in Aldara‐treated and lesional psoriatic skin, but IL‐17A and IL‐12p40 were significantly underexpressed in Aldara‐treated skin compared with lesional psoriatic skin. IL‐10 was significantly overexpressed in Aldara‐treated skin. Conclusions: We were able to induce psoriasis‐like skin inflammation although typical psoriasis did not develop, possibly due to incomplete adaptive immune system recruitment and the powerful stimulation of IL‐10 counter‐regulation.